Butterfly Optimizer for Placement and Sizing of Distributed Generation for Feeder Phase Balancing - Mishra S.; Kumar A.; Singh D.; Kumar Misra R. (My University, 2025)
The present work investigates a new strategy of applying single-phase distributed generations (DGs) for the problem of phase load balancing. The work demonstrates that single-phase DG can be applied at specific location and phase so that overall phase loads are balanced at the root node. The problem of suitable size, bus-phase location of DGs is a mixed integer nonlinear programming (MINLP) problem. This problem is attempted using butterfly optimizer to get solution. © 2019, Springer Nature Singapore Pte Ltd.